Turning The Spirit and Awareness of Reading the Qur'an in a Ṣaḥīḥ According to Riwāyah Mutawātirah Through the Talaqqi Program at the Ittihadul Muwahidin Pati Islamic Boarding School - Farah Shafa Aulia; Muna Ikromatussofia; Eska Perdana Prasetya (Universitas Ibn Khaldun, 2025)
This study aims to revive the spirit and awareness of reading the Qur’an correctly (ṣaḥīḥ) in accordance with riwāyah mutawātirah through the talaqqi program at Pesantren Islam Ittihadul Muwahidin, Pati. The background of this research stems from the varying abilities of female students in reading the Qur’an, where errors in tajwīd, makhārij al-ḥurūf, and the characteristics of letters were still found. The research method employed is qualitative with an observational approach and narrative analysis through ḥalaqah activities. The implemented programs include “Easy and Enjoyable Tahsin” and “Intensive Tahsin Workshop with Sanad” standardized by the riwāyah Ḥafṣ ‘an ‘Āṣim. The results show an improvement in the quality of students’ recitation, indicated by the majority achieving grades ranging from good to mumtāz in evaluations. In addition, the talaqqi method proved effective in fostering learning motivation and creating a conducive learning atmosphere. This study concludes that the application of talaqqi can serve as an important means of improving Qur’anic recitation while also building students’ awareness to continuously love the Qur’an.